The fugitive race : minority writers resisting whiteness - Knadler, Stephen P., 1963- (University Press of Mississippi, 2002)
Denying its formative dialogues with minorities, the white race, Stephen P. Knadler contends, has been a fugitive race. While the "white question," like the "Negro question," and the "woman question" a century earlier, has garnered considerable critical attention among scholars looking to find new anti-race strategies, these investigations need to highlight not just the exclusion of people of color, but also examine minority writers' resistance to and disruption of this privileged racial category. "Highly original, wonderfully detailed, and thought provoking